2018
DOI: 10.3389/fmicb.2018.02648
|View full text |Cite
|
Sign up to set email alerts
|

A Screening Method for the Isolation of Bacteria Capable of Degrading Toxic Steroidal Glycoalkaloids Present in Potato

Abstract: Potato juice, a by-product of starch processing, is a potential high-value food ingredient due to its high protein content. However, conversion from feed to human protein requires the removal of the toxic antinutritional glycoalkaloids (GAs) α-chaconine and α-solanine. Detoxification by enzymatic removal could potentially provide an effective and environmentally friendly process for potato-derived food protein production. While degradation of GAs by microorganisms has been documented, there exists limited know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…The results showed that the concentration of α-solanine in the cecum increased obviously with B. coagulans R11 feeding. α-Solanine was one of the alkaloids that can be commonly found in potatoes, and most previous studies focused on only the degradation of α-solanine (Hennessy et al, 2018(Hennessy et al, , 2019. Hennessy found that Arthrobacter sp.…”
Section: α-Solanine Was a Major Alkaloid Metabolite In The B Coagulamentioning
confidence: 99%
“…The results showed that the concentration of α-solanine in the cecum increased obviously with B. coagulans R11 feeding. α-Solanine was one of the alkaloids that can be commonly found in potatoes, and most previous studies focused on only the degradation of α-solanine (Hennessy et al, 2018(Hennessy et al, , 2019. Hennessy found that Arthrobacter sp.…”
Section: α-Solanine Was a Major Alkaloid Metabolite In The B Coagulamentioning
confidence: 99%
“…To convert starch side streams from feed to food, antinutritional factors, including GAs, must be removed. While fungal pathogens are known to degrade potato-derived GAs, little information on bacterial enzymes is available (2). This announcement reports the draft genome sequences of two Arthrobacter strains (S39 and S41) which are capable of degrading α-chaconine and α-solanine.…”
Section: Announcementmentioning
confidence: 99%
“…S39 and Arthrobacter sp. S41 were isolated from green potato peel (2). Genomic DNA was purified from liquid cultures grown at 20°C in lysogenic broth (LB) using the Gentra Puregene Yeast/Bact.…”
Section: Announcementmentioning
confidence: 99%
“… Serratia sp. strain S40 was isolated from a potato rhizosphere in Zealand, Denmark ( 5 ). For whole-genome sequencing, the strain was cultivated in lysogeny broth (LB) for 24 h at 20°C before DNA extraction.…”
Section: Announcementmentioning
confidence: 99%
“…Genomic DNA was purified using the Gentra Puregene Yeast/Bact. kit (Qiagen, Germany) according to the manufacturer’s instructions, and purified genomic DNA was verified by 16S RNA gene sequencing as previously described ( 5 ). Library preparation for whole-genome sequencing was performed using the Nextera DNA library prep kit (Illumina, Inc., San Diego, CA, USA).…”
Section: Announcementmentioning
confidence: 99%